Physiological and biochemical responses of rice to polyethylene glycol (Bangladesh Journal of Botany, 2023)
Effects of water deficit induced by polyethylene glycol (PEG-6000) on rice grown in half strength Hoagland solution was studied in the present investigation. Impacts of different water stress (10, 20 and 30% PEG) on some physiological and biochemical characteristics were determined in this investigation. Results showed that water stress significantly affected most physiological and biochemical characteristics. The increasing water stress declined the root and shoot length and fresh and dry weights of root and shoot. An increase in water stress also resulted in reduction of relative water content, leaf pigments and protein content. Upon dehydration, an incline in reducing and total sugar and proline content were evident in the root and shoot of rice. Water-deficit stress resulted in higher superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities but as the severity of the water stress increased, the SOD activity decreased. These crucial characteristics would be expected to be utilized as screening techniques for water stress tolerance to the future development of new variety.Bangladesh J. Bot. 52(4): 897-905, 2023 (December)